Features of Compensation for Damage Caused to Natural Resources in Kazakhstan - ABDUKARIMOVA, Zhanar; BITEMIROV, Kairat; BIZHAN, Nurlan; ESENALIYEV, Askat; POSHANOV, Nursultan; KALKANOVA, Zhanna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).01, 2018)
The issues related to compensation for damage caused to natural resources as a result of economic activity are examined in the presented article. Problems of compensation for damage to natural resources are in the focus of attention of domestic and foreign researchers. At the same time, there is a need to continuously improve the legal mechanism of compensation for damage to increase its effectiveness. The purpose of this article is to study the existing approaches to compensation for damage caused to natural resources to elaborate effective solutions in this area. The article presents various approaches to compensation for damage to natural resources in Kazakhstan and abroad. A comparative legal analysis of the establishment of environmental liability for causing damage to the environment was conducted in the law and order of Kazakhstan and foreign countries. The legislative regulation in Kazakhstan of compensation for damage caused to natural resources was also assessed from the point of view of the general theory of environmental law and constitutional and legal principles. The issues of compensation of damage caused to natural resources using the tax approach were considered. Based on the extensive analysis of literature, a generalized model of compensation for damage caused to natural resources was presented, with particular attention to the fact that the responsibility for causing damage to the environment under Kazakhstan's law consisted in imposing on the party which caused the damage the obligation to eliminate the damage caused to the environment or compensate for it in another way, both in value form and in kind. The author also developed proposals on improving statutory regulation in the sphere of compensation for damage in Kazakhstan